Illegal practices of management in the public sector on accountants and the important role of the auditor in reducing them - mohamed ali wahab, asaad; Abdel Karim Mohsen, Sara (Journal of Research in Finance and Accounting, 2026)
The research aims to know the role of external audit in enhancing the performance of accountants and reducing the pressures they are exposed to from the administrations to cover up their sometimes-illegal practices. To achieve the objectives of the research, the descriptive approach was followed to suit the nature of the subject of the research. A 28-paragraph questionnaire was designed as a tool for data collection. 140 of them were distributed, and the validity of the analysis was 130. The research reached agreement among the sample members on the absence of sufficient legal protection for accountants, which may help accountants acquiesce to the pressures of the administration. The researchers recommended that the work of accountants objectively and impartially, there must be a law that guarantees protection for the accountant in the event that he is punished in the case of his reservation on the illegal practices of management.